(x-1)(6x+2)=(2x+8)(3x-6)

Simple and best practice solution for (x-1)(6x+2)=(2x+8)(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(6x+2)=(2x+8)(3x-6) equation:


Simplifying
(x + -1)(6x + 2) = (2x + 8)(3x + -6)

Reorder the terms:
(-1 + x)(6x + 2) = (2x + 8)(3x + -6)

Reorder the terms:
(-1 + x)(2 + 6x) = (2x + 8)(3x + -6)

Multiply (-1 + x) * (2 + 6x)
(-1(2 + 6x) + x(2 + 6x)) = (2x + 8)(3x + -6)
((2 * -1 + 6x * -1) + x(2 + 6x)) = (2x + 8)(3x + -6)
((-2 + -6x) + x(2 + 6x)) = (2x + 8)(3x + -6)
(-2 + -6x + (2 * x + 6x * x)) = (2x + 8)(3x + -6)
(-2 + -6x + (2x + 6x2)) = (2x + 8)(3x + -6)

Combine like terms: -6x + 2x = -4x
(-2 + -4x + 6x2) = (2x + 8)(3x + -6)

Reorder the terms:
-2 + -4x + 6x2 = (8 + 2x)(3x + -6)

Reorder the terms:
-2 + -4x + 6x2 = (8 + 2x)(-6 + 3x)

Multiply (8 + 2x) * (-6 + 3x)
-2 + -4x + 6x2 = (8(-6 + 3x) + 2x * (-6 + 3x))
-2 + -4x + 6x2 = ((-6 * 8 + 3x * 8) + 2x * (-6 + 3x))
-2 + -4x + 6x2 = ((-48 + 24x) + 2x * (-6 + 3x))
-2 + -4x + 6x2 = (-48 + 24x + (-6 * 2x + 3x * 2x))
-2 + -4x + 6x2 = (-48 + 24x + (-12x + 6x2))

Combine like terms: 24x + -12x = 12x
-2 + -4x + 6x2 = (-48 + 12x + 6x2)

Add '-6x2' to each side of the equation.
-2 + -4x + 6x2 + -6x2 = -48 + 12x + 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
-2 + -4x + 0 = -48 + 12x + 6x2 + -6x2
-2 + -4x = -48 + 12x + 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
-2 + -4x = -48 + 12x + 0
-2 + -4x = -48 + 12x

Solving
-2 + -4x = -48 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-2 + -4x + -12x = -48 + 12x + -12x

Combine like terms: -4x + -12x = -16x
-2 + -16x = -48 + 12x + -12x

Combine like terms: 12x + -12x = 0
-2 + -16x = -48 + 0
-2 + -16x = -48

Add '2' to each side of the equation.
-2 + 2 + -16x = -48 + 2

Combine like terms: -2 + 2 = 0
0 + -16x = -48 + 2
-16x = -48 + 2

Combine like terms: -48 + 2 = -46
-16x = -46

Divide each side by '-16'.
x = 2.875

Simplifying
x = 2.875

See similar equations:

| -(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3 | | 2+4X=4-(x-3) | | 2[m+1]=16 | | =364x | | 9e+4e+7f+2f= | | 6x^2+18xy^2-24xy= | | 25x=150-65 | | 13+2[5c-2]=29 | | 14+3x=3+5x+4 | | x^3+10x^2+33x+36=0 | | 2x^2+2y^2+2xy+10x+2y+14=0 | | 8x-(1-5x)=17+7x | | 2(x+10)=7(x+2)-4x | | f(x)=x^3+10x^2+33x+36 | | 105-x-40+3x=150 | | 7c-4=7 | | 3x+12=(x+1) | | 105-35-40+60=150 | | (x+1)(x-6)=(x+5)(x-2) | | 4x-2x=3(x-3) | | 16x^3-28x^2+4x=-8x | | 7x-11=5(x-2)+2x | | x^3+2x^2=80x | | 7(3n-3)=(7n+7)+4 | | 5x+7=.5(10x+12) | | 5x+7=1.2(10x+12) | | 35(3-x)-20(2-3x)=150 | | 3=-3/5(m-9) | | 3+35x=15x+7 | | 2c-6=4c+4 | | x-(-8)=-32 | | 4v+2-2(-8v-1)=2(v-3) |

Equations solver categories